2005
DOI: 10.1007/s00262-005-0001-1
|View full text |Cite
|
Sign up to set email alerts
|

T-cell activation and B-cell depletion in chimpanzees treated with a bispecific anti-CD19/anti-CD3 single-chain antibody construct

Abstract: BscCD19xCD3 is a bispecific single-chain antibody construct with exceptional cytotoxic potency in vitro and in vivo. Here, we have investigated the biological activity of bscCD19xCD3 in chimpanzee, the only animal species identified in which bscCD19xCD3 showed bispecific binding, redirected B-cell lysis and cytokine production comparable to human cells. Pharmacokinetic analysis following 2-h intravenous infusion of 0.06, 0.1 or 0.12 mug/kg of bscCD19xCD3 as part of a dose escalation study in a single female ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 25 publications
4
44
0
1
Order By: Relevance
“…A key difference was EpCAM expression on mouse lymphocytes, which was not seen on human lymphocytes. As reported for the B-lymphocyte-specific BiTE antibody MT103 in chimpanzee, the immediate encounter of T cells and B target cells in blood can cause transient cytokine release by MT103 (47). This may be less pronounced with a BiTE targeting localized EpCAM target in tumor tissue.…”
Section: Murine-specific Epcam Bitementioning
confidence: 96%
“…A key difference was EpCAM expression on mouse lymphocytes, which was not seen on human lymphocytes. As reported for the B-lymphocyte-specific BiTE antibody MT103 in chimpanzee, the immediate encounter of T cells and B target cells in blood can cause transient cytokine release by MT103 (47). This may be less pronounced with a BiTE targeting localized EpCAM target in tumor tissue.…”
Section: Murine-specific Epcam Bitementioning
confidence: 96%
“…MT103, a CD19-specific BiTE, showed a high ex vivo response against blood samples from B-cell lymphoma patients (Loffler et al, 2003), and was efficacious in a severe combined immunodeficiency (SCID) mouse model (Dreier et al, 2003a). It has been shown in chimpanzees that MT103 causes cumulative loss of peripheral B lymphocytes (Schlereth et al, 2006). A clinical trial testing the prolonged administration of bscCD19xCD3 (MT103) for improving efficacy is currently ongoing.…”
Section: Bispecific Antibodiesmentioning
confidence: 99%
“…15 The CD19xCD3 BiTE molecule (blinatumomab) was further evaluated in chimpanzees, and significant B-cell depletion was observed. 16 Moreover, results from early clinical studies of blinatumomab have demonstrated impressive response rates in both relapsing nonHodgkin lymphoma and B-cell acute lymphoblastic leukemia patients, supporting further evaluation of this potential therapeutic avenue. 17 Despite this success, scFv-based bispecific strategies have limitations, including constraints imparted by the linker sequences that connect the V regions in a "nonnatural" manner, resulting in reduced or altered antigen recognition and potency.…”
Section: Introductionmentioning
confidence: 99%